Analisis Strategi Pengembangan Destinasi Pariwisata Kawasan Kota Lama Kota Surabaya - Bonifasius Deva Putratama; Singgih Manggalou (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This research aims to analyze the strategies for developing tourism destinations in the Old Town area of Surabaya, focusing on the formulation, implementation, and evaluation of these strategies. The method used is descriptive analysis with a qualitative approach. Data collection techniques consist of observation, interviews, and documentation, with informants from the Department of Culture, Youth, and Sports and Tourism, tour guides, and tourists. The research results indicate that Surabaya's Old Town has significant potential as a heritage tourism destination, evidenced by the increasing trend in historical tourism, an active historical community, and well-preserved colonial buildings. The area development strategy is realized thru building revitalization programs, space utilization, improved accessibility, and the development of MSMEs. Tourism promotion is carried out thru Famtrip activities, cultural attractions, and thematic tourism such as jeep tours and tourwagen, which have proven to enhance the positive image of the area. However, several obstacles are still encountered, including limited public facilities, security, street vendor management, and competition with other heritage destinations. Evaluation shows that cross-agency collaboration, CSR support, and community participation play an important role in achieving sustainable development. Thus, the development of Surabaya's Old Town not only emphasizes the preservation of heritage values but is also able to make a real contribution to the local economy and the city's image.